2009
DOI: 10.1074/jbc.m809269200
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of HIV-1 Inhibitory Peptide T20 with the gp41 N-HR Coiled Coil

Abstract: Cellular entry of human immunodeficiency virus type 1 (HIV-1) involves fusion of viral and cellular membranes and is mediated by structural transitions in viral glycoprotein gp41. The antiviral C-peptide T20 targets the gp41 N-terminal heptad repeat region (N-HR), blocking gp41 conformational changes essential for the entry process. To probe the T20 structure-activity relationship, we engineered a molecular mimic of the entire gp41 N-HR coiled coil using the 5-Helix design strategy. T20 bound this artificial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 45 publications
6
72
2
Order By: Relevance
“…Second, we demonstrated that the magnitude of synergy between CoRAs and C-peptides like T20 depended on C-peptide-binding affinity, with maximal synergy observed for very high-affinity C-peptide variants, whereas mere additivity was measured for low-affinity C-peptide variants. With T20 having only a modest affinity for gp41 (52), discrepancies in the N-HR sequences of Envs used in different studies could be a source of variability. Finally, we determined that the number of coreceptor binding events required for CoRA/FI synergy exceeded the number required for HIV-1 entry.…”
Section: Complex Synergy Mechanisms Of Hiv-1 Entry Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, we demonstrated that the magnitude of synergy between CoRAs and C-peptides like T20 depended on C-peptide-binding affinity, with maximal synergy observed for very high-affinity C-peptide variants, whereas mere additivity was measured for low-affinity C-peptide variants. With T20 having only a modest affinity for gp41 (52), discrepancies in the N-HR sequences of Envs used in different studies could be a source of variability. Finally, we determined that the number of coreceptor binding events required for CoRA/FI synergy exceeded the number required for HIV-1 entry.…”
Section: Complex Synergy Mechanisms Of Hiv-1 Entry Inhibitorsmentioning
confidence: 99%
“…In these experiments, we used HIV-1 pseudotyped with CXCR4-tropic Env HXB2 , U87-CD4-CXCR4 target cells, and CoRA AMD3100. The FI was C37, a well-characterized C-peptide with a binding site that overlaps that for T20 (38,52). As with maraviroc/T20 combinations in Fig.…”
Section: Dependence Of C-peptide Fi/cora Synergy On C-peptidebinding mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the pocket-forming sequence in NHR is regarded as the primary binding site for T1144. This may explain why T1144 and other CHR peptides with pocketbinding sequences, e.g., C34, C37, and C38, bind to the gp41 NHR domain much more strongly than T20 and are more effective than T20 in blocking gp41 6-HB formation (2,6,25,29,30). Since the region of aa 36 to 45 is not the primary binding site for T1144, the T20-resistant viruses with mutations in this region are sensitive to T1144 (Table 2).…”
mentioning
confidence: 98%
“…The long groove presented by Fe(env5.0) 3 includes both the hydrophobic pocket and a proximal groove that is the target of the N-terminal 60% of T20. This N-terminal segment is considered to play an important role in the interaction of T20 with the NHR (2,26). Small molecules targeting the proximal groove may conceivably be linked to hydrophobic pocket binders to create a highly potent inhibitor.…”
Section: Vol 53 2009 Coiled-coil Receptor Design For Hiv-1 Assay 2447mentioning
confidence: 99%